Instrumentel intimitet - Carlsen, Linus (Passage - Tidsskrift for litteratur og kritik, 2019)
The article traces some of the major variations in depictions of the humanoid robot – the android – as a figure that negotiates existential issues such as work, subjectivity and intimacy. Via analyses of intimate relationships in works by Philip K. Dick, Isaac Asimov and Alissa Nutting, the article discusses how the android in the literary imaginary presents us with a vision of instrumental intimacy in the 21st century and the limits thereof.